Developing learning and training within industry model to improve work readiness of vocational high school students - Bambang Sudarsono; Prabandari Listyaningrum; Fatwa Tentama; Fanani Arief Ghozali (Institute of Advanced Engineering and Science, 2024)
Unemployment is still a national priority that needs to be addressed. In 2022, vocational high schools in Indonesia had the highest open unemployment rate. The highest open unemployment rate is a result of vocational high school students’ insufficient work readiness. Therefore, this research aims to develop a learning and training within industry (LTWI) model, and to evaluate the model’s efficacy in increasing vocational high school students’ work readiness. The research employed a research and development (R&D) design by Richey and Klein with the phases of needs analysis, internal validation, and external validation. There were 12 teachers and 89 students from the automotive engineering department at Muhammadiyah 1 Pakem Vocational High School and 1 Puring Vocational High School, as well as six instructors from the automotive industry: GAS Auto Service, Automotive Jogjakarta Center (OJC), Bengkel Barokah, and RND Auto Service, participated in the research. Data collection strategies adopted were interviews, questionnaires, and performance tests. The data were descriptively evaluated, and the conclusions were drawn using a categorization formula. With an average score of 3.43, the LTWI model can be used to learn very well. With an average final score of 3.32, the efficacy of the LTWI learning model falls into the category of “very good”. The LTWI model can be applied effectively to learning in vocational high schools since it has a positive influence on students’ work readiness.